(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Ellumthippallyadi Lehya is one among the classical lehya formulation mentioned in sahasrayogam. Lehya formulations are often sticky, dense, and may have a strong odor, which can be unappealing, especially for sensitive individuals. Dosage accuracy can also vary with difference in consistency. Candies, though primarily consumed for taste and pleasure are increasingly being explored for their potential as carriers for therapeutic agents. Development of new dosage forms and ensuring their quality and safety through pharmaceutical standardization is essential for their acceptance especially in health focused formulations. Ellumthippallyadi Lehya Yoga was converted to a candy as a modified dosage form with a uniform weight of 3g. Machinery support was used for the production of candies. The drugs were taken in the ratio as mentioned in the reference. The constituents in one candy were adjusted considering the amount of Loha bhasma as 50 mg in each candy. The candies were made using palm sugar candy as base and liquid glucose was added for desired consistency. Elluthippallyadi Lehya Candy was subjected to standard pharmaceutical evaluations, including organoleptic properties, weight variation, and Disintegration time, pH, and heavy metal analysis using standard methods. The Ellumthippallyadi Lehya candy demonstrated compliance with standard pharmaceutical parameters and its other safety parameters ensured its potential as a convenient dosage form.